An acoustically powered Janus hydrogel and methods of making and using the same

CN121731202BActive Publication Date: 2026-10-20ANHUI UNIVERSITY OF TRADITIONAL CHINESE MEDICINE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511990623.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-26
Publication Date
2026-10-20
Estimated Expiration
2045-12-26

AI Technical Summary

Technical Problem

然而现有Janus水凝胶多聚焦于伤口愈合或器官修复,未见有与声动力技术结合来预防牙周炎中细菌粘附的文献报道

Benefits of technology

本发明提供的声动力驱动的Janus水凝胶能够超声驱动释放ROS,破坏细菌生物膜,与Ag2O2缓释的Ag+协同实现高效杀菌效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121731202B_ABST
    Figure CN121731202B_ABST
Patent Text Reader

Abstract

The application discloses a kind of Janus hydrogel driven by acoustic power and its preparation method and application, the hydrogel includes silver peroxide and hydrogel matrix;The hydrogel matrix is composed of methacrylated silk fibroin, gamma-polyglutamic acid-N-hydroxysuccinimide ester and photoinitiator.The hydrogel prepared by component synergy and structural innovation can release ROS according to ultrasonic driving, destroy bacterial biofilm, and realize efficient sterilization effect with the slow-release Ag of Ag2O2 + Synergy;The hydrogel can form Janus structure with one side adhering and the other side anti-adhesion after ultraviolet light crosslinking.The pharmacodynamic experimental results show that the Janus hydrogel driven by acoustic power prepared by the application has excellent antibacterial effect, can be used to promote wound healing, repair alveolar bone defect and the like, and also provides a new choice for infection or skin wound repair of periodontitis, oral mucosa inflammation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of gel biomaterials, and particularly relates to an acoustically driven Janus hydrogel, its preparation method, and its application. Background Technology

[0002] Periodontitis is a common chronic inflammatory disease. Bacterial infection is the main pathogenic factor of periodontitis. Plaque microorganisms and their toxic metabolites act on periodontal tissues for a long time, and neutrophils and lymphocytes infiltrate the infected site, causing progressive destruction of these tissues, leading to gingival swelling, attachment loss, alveolar bone resorption, and periodontal pocket formation. If not intervened in time, it can lead to tooth loosening and even tooth loss. Current traditional antibacterial treatments for periodontitis include subgingival scaling and the use of antibacterial drugs. However, these methods have significant limitations. First, subgingival scaling requires high patient cooperation, but due to the complexity of the procedure and the potential for discomfort, patient compliance is poor, resulting in unstable treatment effects and easy repeated colonization of bacterial biofilms. In addition, clinically used topical antibacterial drugs such as minocycline hydrochloride, metronidazole, and chlorhexidine, while effective against free-living bacteria, are ineffective against bacteria encapsulated in biofilms. Furthermore, prolonged use of antibiotics may lead to increased bacterial resistance. Therefore, the key to antibacterial treatment for periodontitis lies in how to remove bacterial biofilms, enhance host immunity, and inhibit subsequent bacterial adhesion in order to effectively suppress disease progression.

[0003] Addressing the difficulty in removing periodontal bacterial biofilms, antibacterial sonodynamic therapy (aSDT) is an emerging antibacterial technology. Its principle involves using ultrasound to activate a sonosensitive agent, generating reactive oxygen species (ROS) to kill bacteria. Compared to traditional antibiotic treatment, aSDT offers advantages such as superior tissue penetration, high biocompatibility, and no induction of drug resistance. This therapy concentrates ultrasonic energy at the infection site, activating the sonosensitive agent to produce highly cytotoxic ROS, thereby inducing bacterial death. However, when used alone, it has drawbacks such as limited ROS activity and potential damage to normal tissues.

[0004] The human oral cavity is a moist and open complex microbial ecosystem. This environment not only contains a large amount of saliva but also allows for the presence of bacteria and other microorganisms. The fluidity of saliva and the openness of the oral cavity pose a risk of drug erosion during local administration, making it difficult to maintain drug concentration in the target treatment area. Furthermore, timely and effective removal of bacterial biofilms allows free bacteria to rapidly colonize the periodontal tissue surface.

[0005] Janus hydrogels are a class of hydrogels with distinct functions on both sides. Their asymmetric chemical or physical properties endow them with unique properties and broad application prospects. In the fields of materials science and biomedicine, Janus hydrogels have attracted attention because they can achieve different adhesion properties by modulating the functional groups on both sides. However, existing Janus hydrogels mainly focus on wound healing or organ repair, and there are no literature reports on their combination with sonodynamic technology to prevent bacterial adhesion in periodontitis. Summary of the Invention

[0006] To address the aforementioned problems, the present invention aims to provide a sonodynamically driven Janus hydrogel, its preparation method, and its applications. The sonodynamically driven Janus hydrogel prepared by the present invention has excellent antibacterial properties, can significantly repair alveolar bone defects, and can also improve the healing efficiency of skin wounds, providing a new option for the repair of infections such as periodontitis and oral mucosal inflammation, or skin trauma.

[0007] This invention is achieved through the following technical solution: A sonodynamically driven Janus hydrogel comprising silver peroxide (Ag2O2) and a hydrogel matrix; the hydrogel matrix is ​​composed of methacrylamide silk fibroin (SFMA), γ-polyglutamic acid-N-hydroxysuccinimide ester (γ-PGA-NHS), and a photoinitiator.

[0008] γ-Polyglutamic acid (γ-PGA), also known as natto gum, is a water-soluble, biodegradable, and non-toxic natural anionic polyamino acid, typically produced on a large scale through fermentation engineering. To enhance its adhesiveness, it is modified with NHS, resulting in γ-PGA-NHS, which exhibits excellent cell compatibility and high reactivity to primary amines.

[0009] This invention uses methacrylamide silk fibroin (SFMA) and γ-polyglutamic acid-N-hydroxysuccinimide ester (γ-PGA-NHS) as the hydrogel matrix. SFMA exhibits excellent biocompatibility, biodegradability, and tissue repair capabilities, while γ-PGA-NHS demonstrates excellent tissue adhesion. A dual crosslinking system is a common and effective strategy for achieving enhanced mechanical strength and strong adhesion. Upon UV irradiation, a dual crosslinking network is formed. In this system, some of the NHS ester groups of γ-PGA-NHS bind to the amino groups on SFMA, resulting in crosslinking. Additionally, SFMA crosslinks upon light irradiation with a photoinitiator. Rapid curing into a dual crosslinking structure provides sufficient mechanical strength while simultaneously forming strong adhesion and a physical barrier, ultimately inhibiting subsequent bacterial adhesion.

[0010] In a preferred embodiment of the present invention, the hydrogel further includes titanium carbide nanosheets, on which silver peroxide is loaded.

[0011] Titanium carbide nanosheets are two-dimensional layered materials with excellent ultrasonic response and high specific surface area. This invention uses titanium carbide nanosheets as a carrier for silver peroxide, which not only improves the stability and dispersibility of Ag₂O₂, but also because the titanium carbide nanosheets themselves possess certain acoustic sensitivity properties, synergistically enhancing the acoustic dynamics effect with Ag₂O₂.

[0012] In a preferred embodiment of the present invention, the titanium carbide nanosheets are further loaded with caffeic acid phenethyl ester (CAPE). CAPE can not only inhibit the release of inflammatory factors, but also remove residual ROS to avoid tissue damage.

[0013] In a preferred embodiment of the present invention, the mass ratio of the photoinitiator, titanium carbide nanosheets loaded with caffeic acid phenethyl ester and silver peroxide, methacrylamide silk fibroin and γ-polyglutamic acid-N-hydroxysuccinimide ester in the hydrogel is 1:40:40-120:40.

[0014] In a preferred embodiment of the present invention, the photoinitiator is at least one of phenyl-2,4,6-trimethylbenzoyl lithium phosphine oxide (LAP), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, or 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone.

[0015] The present invention also provides a method for preparing the above-mentioned acoustically driven Janus hydrogel, comprising the following steps: (1) Preparation of precursor solution A: Silver peroxide, photoinitiator and methacrylamide silk fibroin (SFMA) were dissolved in deionized water and mixed evenly to obtain precursor solution A; (2) Preparation of precursor solution B: γ-polyglutamic acid-N-hydroxysuccinimide ester (γ-PGA-NHS) was dissolved in NaHCO3 solution to obtain precursor solution B; (3) Ultraviolet curing: Precursor solution A and precursor solution B are mixed and cured by ultrasound and ultraviolet light to obtain acoustically driven Janus hydrogel.

[0016] In a preferred embodiment of the present invention, in step (1), titanium carbide nanosheets are modified with aminosilane to obtain Ti3C2-NH2; then Ti3C2-NH2 is dissolved in an ethanol solution, and silver peroxide and / or phenethyl caffeate are added sequentially. After stirring, the precipitate is obtained by centrifugation and washing. Titanium carbide nanosheets loaded with silver peroxide and / or phenethyl caffeate are obtained.

[0017] In a preferred embodiment of the present invention, the stirring temperature is 25-37°C and the stirring time is 4-24 hours.

[0018] In a preferred embodiment of the present invention, the mass ratio of Ti3C2-NH2 to phenethyl caffeate is 1:15-30; and the mass ratio of Ti3C2-NH2 to silver peroxide is 1:1-3.

[0019] In a preferred embodiment of the present invention, the power of the ultrasound is 1~1.2 W / cm². 2 50% duty cycle, frequency of 1~1.5MHz, duration of 2~3min.

[0020] In a preferred embodiment of the present invention, the wavelength of the ultraviolet light is 365~405 nm, and the curing time is 6~10 s.

[0021] This invention also provides the above-mentioned acoustically driven Janus hydrogel for the preparation of products for the prevention or treatment of periodontitis or oral mucosa. Application in anti-inflammatory drugs.

[0022] The Janus hydrogel of this invention is driven by ultrasound to release ROS, which destroys bacterial biofilms. Then it is cured by ultraviolet light, so that the side of the hydrogel close to the tissue forms an adhesion surface (covalently bonded to periodontal soft tissue) and the side facing the oral cavity forms an anti-adhesion surface, forming an anti-adhesion barrier, inhibiting the subsequent adhesion of free bacteria and preventing the formation of bacterial biofilms.

[0023] The present invention also provides the application of the above-mentioned acoustically driven Janus hydrogel in the preparation of skin wound repair materials, especially suitable for the repair of skin wounds infected with bacteria.

[0024] Compared with the prior art, the present invention has the following advantages: The acoustically driven Janus hydrogel provided by this invention can release ROS through ultrasound, disrupting bacterial biofilms, and releasing Ag2O2 in a slow-release manner. + They work together to achieve a highly efficient sterilization effect.

[0025] Pharmacodynamic experiments showed that the sonodynamically driven Janus hydrogel prepared in this invention significantly inhibited Porphyromonas gingivalis and Fusobacterium nucleatum in rats with periodontitis, exhibiting excellent antibacterial activity and significantly repairing alveolar bone defects, providing a new option for treating periodontitis or oral mucosal inflammation.

[0026] In addition, the Janus hydrogel driven by acoustic dynamics of the present invention can also improve the healing efficiency of skin wounds, reduce bacterial infection and inflammatory response, and is suitable for skin wound repair materials. Attached Figure Description

[0027] Figure 1 In the embodiments of the present invention, Ti3C2, Ag2O2, and TAG are used. 、 Scanning electron microscope and EDS images of TCAg; Figure 2 The Ti3C2, Ti3C2-NH2, Ag2O2, and TAG in the embodiments of the present invention 、 Potential diagram of TCAg; Figure 3 The following are acoustic dynamic diagrams of Ti3C2, TAg, and TCAg in embodiments of the present invention; Figure 4 The above are the proton nuclear magnetic resonance spectra of SFMA and γ-PGA-NHS in the embodiments of the present invention; Figure 5 The scanning electron microscope image of TCAg@SMP in an embodiment of the present invention; Figure 6 The asymmetric adhesion of TCAg@SMP in the embodiments of the present invention; Figure 7 This is an evaluation of the inhibitory effect of TCAg@SMP on bacterial adhesion in the embodiments of the present invention; Figure 8 This is a bacterial plating plate diagram of Ti3C2, Ag2O2, and TCAg in an embodiment of the present invention; Figure 9 These are SEM images of Ti3C2, Ag2O2, and TCAg bacteria from embodiments of the present invention; Figure 10 This embodiment of the invention illustrates the changes in periodontal bacterial levels in rats with periodontitis after gel treatment. Figure 11 This is an example of the gel's effect on the repair of posterior alveolar bone in rats with periodontitis in an embodiment of the present invention; Figure 12 The following is an example of the healing changes of rat wounds treated with gel from day 0 to day 14 in an embodiment of the present invention. Detailed Implementation

[0028] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. The described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0029] (1) Preparation of carbon nanosheets (Ti3C2): 1.0 g LiF powder was added to 20 mL of 9 mol / L hydrochloric acid solution and mixed for 30 min. Then, 1.0 g Ti3AlC2 powder was slowly added and reacted in an oil bath at 45 °C for 24 h. The product was washed by centrifugation several times until neutral and then dried under vacuum at 60 °C for 12 h to obtain multilayer Ti3C2. Subsequently, it was dispersed in deionized water and ultrasonically exfoliated at 400 W for 4 h. After centrifugation at 3500 r / min for 60 min, the supernatant was collected and freeze-dried to obtain monolayer Ti3C2.

[0030] (2) Preparation of Ag2O2: 0.5 g of PVP was dissolved in an aqueous solution containing AgNO3 (5 mL, 20 mM). Then, NaOH (5 mL, 20 mM) and H2O2 (100 μL, 30%) were added sequentially. After stirring for 30 minutes, Ag2O2 nanoparticles were collected by centrifugation and washed multiple times with ultrapure water and ethanol. Finally, the product was freeze-dried at low temperature to obtain Ag2O2.

[0031] (3) Preparation of methacrylamide silk fibroin (SFMA): 10 g of silk fibroin (SF) was dissolved in 50 mL of 9.3 M LiBr solution and stirred until completely dissolved. Then, 5 mL of glycidyl methacrylate was slowly added, and the mixture was reacted in a water bath at 60 °C for 3 hours. The reaction product was collected and dialyzed against ultrapure water for 3 days. Finally, the reaction solution was freeze-dried to obtain SFMA and stored at -20 °C.

[0032] (4) Preparation of γ-PGA-NHS: 30 wt% γ-PGA-Na + The aqueous solution was first dialyzed against 0.01 M HCl for 24 h, then against ultrapure water for 24 h, and finally lyophilized to obtain the acidic form of γ-PGA. 1 g of the lyophilized γ-PGA was weighed and added to an Erlenmeyer flask containing anhydrous DMSO, purged with nitrogen, and immediately sealed. The mixture was stirred at room temperature with a magnetic stirrer until dissolved. Then, 1.44 g of EDC was added, and after continued stirring until completely dissolved, 4.46 g of NHS was added. After reacting for 24 h, anhydrous ethanol solution was added to precipitate γ-PGA-NHS. The mixture was centrifuged at 3000 rpm for 5 min to remove the supernatant, then washed three times with anhydrous ethanol and once with n-hexane solution. Finally, the product was dried under vacuum to obtain γ-PGA-NHS. Example 1:

[0033] Preparation of precursor solution A: Silver peroxide (Ag2O2), photoinitiator LAP and methacrylamide silk fibroin (SFMA) were dissolved in deionized water and mixed evenly to obtain precursor solution A; Preparation of precursor solution B: γ-polyglutamic acid-N-hydroxysuccinimide ester (γ-PGA-NHS) was dissolved in 7% NaHCO3 solution at pH 8.3 to obtain precursor solution B; Loading the dual syringe: Precursor solution A and precursor solution B are loaded into the two lumens of the dual syringe respectively; wherein the mass ratio of LAP : Ag2O2 : SFMA : γ-PGA-NHS is 1 : 40 : 40 : 40. Example 2:

[0034] Preparation of silver oxide-loaded titanium carbide nanosheets (TAg): 100 μL of 3-aminopropyltriethoxysilane (APTES) was added to Ti3C2 (1 mg / mL, 20 mL), and stirred at 50 °C for 24 h to generate Ti3C2-NH2; Ti3C2-NH2 and Ag2O2 were dissolved in 10 mL of deionized water at a mass ratio of 1:0.5 and stirred. The precipitate was washed with deionized water to obtain silver oxide-loaded titanium carbide nanosheets (TAg). Preparation of precursor solution A: Titanium carbide nanosheets loaded with silver peroxide (TAg), photoinitiator LAP and methacrylamide silk fibroin (SFMA) were dissolved in deionized water and mixed evenly to obtain precursor solution A; Preparation of precursor solution B: γ-polyglutamic acid-N-hydroxysuccinimide ester (γ-PGA-NHS) was dissolved in 7% NaHCO3 solution at pH 8.3 to obtain precursor solution B; Dual syringe loading: Precursor solution A and precursor solution B are loaded into the two lumens of the dual syringe respectively to obtain TAg@ SMP; wherein the mass ratio of LAP : TAg : SFMA : γ-PGA-NHS is 1 : 40 : 40 : 40. Example 3:

[0035] Preparation of titanium carbide nanosheets (TCAg) loaded with caffeic acid phenethyl ester and silver peroxide: 100 μL of 3-aminopropyltriethoxysilane (APTES) was added to Ti3C2 (1 mg / mL, 20 mL) and stirred at 50 °C for 24 h to generate Ti3C2-NH2; Ti3C2-NH2 and CAPE were dissolved in 10 mL of deionized water at a mass ratio of 1:15 and stirred overnight, and then Ag2O2 (Ti3C2-NH2 to Ag2O2 mass ratio of 1:0.5) was added. The precipitate was washed with deionized water to obtain TCAg nanosheets. Preparation of precursor solution A: Titanium carbide nanosheets (TCAg) loaded with caffeic acid phenylethyl ester (CAPE) and silver peroxide (Ag2O2), photoinitiator LAP and methacrylamide silk fibroin (SFMA) were dissolved in deionized water and mixed evenly to obtain precursor solution A; Preparation of precursor solution B: γ-polyglutamic acid-N-hydroxysuccinimide ester (γ-PGA-NHS) was dissolved in 7% NaHCO3 solution at pH 8.3 to obtain precursor solution B; Dual syringe loading: Precursor solution A and precursor solution B are loaded into the two lumens of the dual syringe respectively to obtain TCAg@SMP-10; wherein the mass ratio of LAP : TCAg : SFMA : γ-PGA-NHS is 1 : 40 : 40 : 40. Example 4:

[0036] The mass ratio of Ti3C2-NH2 to CAPE is 1:20, and the mass ratio of Ti3C2-NH2 to Ag2O2 is 1:1; the mass ratio of LAP : TCAg : SFMA : γ-PGA-NHS is 1 : 40 : 80 : 40, resulting in TCAg@SMP-20, and the rest is the same as in Example 3. Example 5:

[0037] The mass ratio of Ti3C2-NH2 to CAPE is 1:25, and the mass ratio of Ti3C2-NH2 to Ag2O2 is 1:2; the mass ratio of LAP : TCAg : SFMA : γ-PGA-NHS is 1 : 40 : 120 : 40, resulting in TCAg@SMP-30, and the rest is the same as in Example 3.

[0038] Example 6: Process Optimization This invention investigated the ratios of Ti3C2-NH2 to CAPE and Ti3C2-NH2 to Ag2O2 using a single-factor method. The results are shown in Tables 1-2 below: Table 1. Effects of different proportions of Ti3C2-NH2:CAPE on the particle size and drug loading of nanosheets (n=3, mean±SD) 1:15 518.24±0.66 90.45±0.63 1:30 522.68±0.70 95.25±0.46 1:45 530.76±0.62 89.60±0.77 As shown in Table 1, the drug loading of TCAg nanosheets gradually increases with the increase of the Ti3C2-NH2:CAPE ratio. However, when the ratio increases to 1:45, the drug loading decreases. The drug loading is highest when the Ti3C2-NH2:Ag2O2 ratio is 1:30. Therefore, the preferred Ti3C2-NH2:CAPE mass ratio is 1:15-30, and more preferably 1:30.

[0039] Table 2 Effects of different ratios of Ti3C2-NH2:Ag2O2 on the particle size and drug loading of nanosheets (n=3, mean±SD) 1:0.5 562.12±0.52 84.8±1.54 1:1.5 545.25±0.67 91.30±0.74 1:3.0 578.64±0.77 88.55±1.12 As shown in Table 2, the drug loading of TCAg nanosheets gradually increases with the increase of the ratio of Ti3C2-NH2:Ag2O2. However, when the ratio increases to 1:3, the drug loading decreases. The highest drug loading is achieved when the ratio of Ti3C2-NH2:Ag2O2 is 1:1.5. Therefore, the preferred mass ratio of Ti3C2-NH2:CAPE is 1:3, and more preferably 1:1.5.

[0040] Example 7: Performance Characterization (1) Characterization of Ti3C2, Ag2O2, TAG and TCAg by scanning electron microscopy and EDS The morphologies of Ti3C2, Ag2O2, TAG, and TCAg were observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The SEM results are shown below. Figure 1 As shown in Figure A, Ti3C2 has a plate-like structure with sharp, blade-like edges, while Ag2O2 consists of spherical particles. Figure 1 (B) Transmission electron microscopy results show that the TAG nanosheets are two-dimensional sheet-like structures with spherical particles distributed on them. Figure 1 (C), TCAg has a sheet-like thickened structure with spherical particles scattered on the surface and a transparent paste-like substance on the outer periphery ( Figure 1 The characterization results of EDS show that Ti, Ag, C, and O elements are uniformly distributed on TCAg. Figure 1 (E).

[0041] (2) Potential characterization of Ti3C2, Ti3C2-NH2, Ag2O2, TAG, and TCAg The potential changes of Ti3C2, Ti3C2-NH2, Ag2O2, TAG, and TCAg were measured, and the results are as follows: Figure 2The results show that Ti3C2 possesses a negative charge (-38.7 ± 1.1 mV) due to the presence of surface hydroxyl groups. The silanol groups of APTES react with the hydroxyl groups of Ti3C2, covalently anchoring the amino groups to the Ti3C2 surface, thereby causing the potential of Ti3C2-NH2 to become positive. This positive surface charge facilitates the subsequent loading of negatively charged Ag2O2 nanoparticles (-14.6 ± 0.3 mV). The potential of TAg is 32.6 ± 1.9 mV, and the potential of TCAg is 21.8 ± 2.4 mV.

[0042] (3) Acoustodynamic properties of Ti3C2, TAG, and TCAg Detection of ROS using 1,3-diphenylisobenzofuran (DPBF) as a molecular probe ( 1 The acoustic-dynamic properties of Ti3C2, TAg, and TCAg were evaluated using US stimulation (1 W / cm²). The acoustic-dynamic properties of Ti3C2, TAg, and TCAg were measured under US stimulation (1 W / cm²). 2 The ability to generate ROS at 50% duty cycle and 1 MHz, such as Figure 3 As shown, the decrease in the characteristic absorption peak of DPBF of Ti3C2 under ultrasonic treatment over time is relatively limited. Figure 3 (A); However, after loading Ag2O2 to form TAG, the characteristic absorbance of DPBF showed a significant time-dependent decrease, indicating that TAG has the ability to generate reactive oxygen species in a time-dependent manner. Figure 3 Similarly, TCAg also exhibits excellent ROS generation performance, indicating that it has good acoustic dynamic effects. Figure 3 (C)

[0043] (4) Characterization of SFMA and γ-PGA-NHS proton NMR spectra use 1 SFMA was characterized by H-NMR ( Figure 4 Compared to SF, SFMA exhibits two new signal peaks at 6.06 ppm and 5.58 ppm, which are signals generated by the two hydrogen nuclei in -CH=CH2, indicating successful synthesis of SFMA. 1 γ-PGA-NHS was characterized by H-NMR ( Figure 4 In the γ-PGA-NHS spectrum (Cb), compared with the γ-PGA spectrum, the peak with a chemical shift of 12.6 ppm (carboxyl proton peak) disappeared, while a new characteristic peak with a chemical shift of 2.7 ppm (NHS ester proton peak) was added, confirming that the carboxyl group of γ-PGA was successfully activated into NHS ester.

[0044] (5) Microstructure characterization of TCAg@SMP prepared in Examples 3-5 The TCAg@SMP mixture prepared in the examples was sputter-coated with gold and then observed using a scanning electron microscope. The results showed that the gel network gradually became denser with increasing SFMA concentration. Figure 5 Furthermore, the presence of nanoparticles can be observed within the gel mesh. Figure 5 ).

[0045] (6) Characterization of the asymmetric adhesion of TCAg@SMP prepared in Examples 3-5 Adhesion-Crosslinking: The adhesion strength of TCAg@SMP was tested using a standardized shear test. Pigskin was cleaned three times before the test and cut into 50 mm × 50 mm squares. An appropriate amount of TCAg@SMP was applied to a piece of pigskin, and then another piece of pigskin was used to cover it, recording the contact area. After irradiating the hydrogel precursor with ultraviolet light (405 nm) for 10 s, the adhesion strength was measured using an electronic universal testing machine (material testing system: MTS standard43, 50N load cell, 10 mm / min). -1 The adhesion strength is tested at the rate of adhesion.

[0046] Crosslinking followed by adhesion: The adhesion strength of TCAg@SMP was tested using a standardized shear test. Before the test, pigskin was cleaned three times and cut into 50 mm × 50 mm squares. An appropriate amount of TCAg@SMP precursor was coated onto a piece of pigskin. The hydrogel precursor was irradiated with ultraviolet light (405 nm) for 10 seconds, and then another piece of pigskin was used to cover it, and the contact area was recorded. An electronic universal testing machine (material testing system: MTS standard43, 50N load cell, 10 mm / min) was used. -1 The adhesion strength is tested at the rate of adhesion.

[0047] Experimental results show that the TCAg@SMP hydrogel exhibits asymmetric adhesion properties. TCAg@SMP-10 represents Example 1, TCAg@SMP-20 represents Example 2, and TCAg@SMP-30 represents Example 3. Figure 6 As shown in Figure A, the pre-adhesive-post-crosslinked TCAg@SMP exhibits strong adhesion to porcine skin tissue. This is attributed to the residual NHS ester groups in the hydrogel, which can form covalent bonds with the amine groups in biological tissue, thereby enhancing interfacial adhesion. The hydrogel prepared in Example 3 showed an adhesion strength of 26.72 ± 0.86 kPa, and the adhesion strength gradually increased with increasing SFMA concentration. Conversely, when TCAg@SMP was photocrosslinked before application to the tissue surface, the resulting hydrogel exhibited extremely low adhesion, with the hydrogel prepared in Example 3 showing an adhesion strength of 5.15 ± 0.23 kPa. Figure 6 (B) This is because the cross-linked network formed after photocuring restricts the movement of NHS ester groups on the hydrogel surface.

[0048] Example 8: Evaluation of the inhibitory effect of TCAg@SMP prepared in Example 3 on bacterial adhesion. Add 1 mL of Porphyromonas gingivalis ( Porphyromonas gingivalis, Pg ) and Fusobacterium nucleatum ( Fusobacterium nucleatum, Fn ) suspension (total 10) 8 CFU / mL was placed in a confocal microplate and incubated for 48 h. The bacterial biofilm was then stained with a mixture of SYTO9 (2.5 μM) and propyl iodide (2.5 μM). Images of the stained, live and dead bacteria were captured using a laser confocal microscope. The bacteria were then sonicated with TCAg@SMP and cured under UV light. The bacterial biofilm was stained again with a mixture of SYTO9 (2.5 μM) and propyl iodide (2.5 μM). Observation was performed using a laser confocal microscope. Then, 100 μL of Pg and Fn suspension (total 10) was added. 8 After culturing for 24 h, the bacterial biofilm was stained with a mixture of SYTO 9 (2.5 μM) and propyl iodide (2.5 μM). Observation was performed using a laser confocal microscope. The control group used confocal dishes without TCAg@SMP, with the remaining procedures the same.

[0049] Experimental results showed that, based on live / dead cell staining, a large number of dead bacteria were found on the glass slides treated with TCAg@SMP hydrogel after sonication. Figure 7 (A-②), while the untreated control showed bacterial biofilm formation ( Figure 7 (B-②). Subsequently, photocrosslinking was performed using TCAg@SMP hydrogel, followed by application of the bacterial suspension to evaluate its anti-adhesion properties. The results showed that a large amount of bacteria proliferated and aggregated on the glass slide (B-②). Figure 7 (B-③). In contrast, in the photocrosslinked TCAg@SMP hydrogel, the NHS ester groups are immobilized in the hydrogel network, resulting in reduced bacterial adhesion ( Figure 7 (A-③). This indicates that TCAg@SMP hydrogel has a potential role in preventing subsequent bacterial adhesion in periodontitis.

[0050] Example 9: Antibacterial performance test of Ti3C2, Ag2O2, and TCAg CFU flat plate coating: In order to make CFU flat plate coating: Pg A single biofilm was formed, and the microbial concentration was adjusted to 10 in a 6-well plate. 8CFU / mL, with a circular glass slide at the bottom of each well. All biofilms were cultured in an anaerobic incubator at 37℃ for 96 h. Five groups were established: Control group, CAPE group, Ti3C2 group, Ag2O2 group, and TCAg group. Different nanomaterials and ultrasound (frequency 1MHz, duty cycle 50%, power 1W / cm²) were used. 2 The biofilm was treated for 3 days. Adhering biofilm was removed using a cell scraper. The solution was then serially diluted 10-fold. 200 µL of the diluted bacterial solution was loaded onto Columbia blood agar.

[0051] Figure 8 Showing Pg In terms of colony-forming unit (CFU) counts, TCAg exhibited the highest efficiency in eliminating bacteria across all test groups.

[0052] SEM bacterial morphology observation: To enable gingival porphyrin to form a single biofilm, the microbial concentration in a 6-well plate was adjusted to 10-1. 8 CFU / mL, with a circular glass slide at the bottom of each well. All biofilms were cultured in an anaerobic incubator at 37℃ for 96 h. Five groups were established: Control group, CAPE group, Ti3C2 group, Ag2O2 group, and TCAg group. Different nanomaterials and ultrasound (frequency 1MHz, duty cycle 50%, power 1W / cm²) were used. 2 The biofilm was treated for 3 days. Then, the glass slide was removed and fixed in glutaraldehyde fixative, followed by dehydration and drying with ethanol of different concentrations. After gold sputtering, its morphology was observed using a scanning electron microscope.

[0053] Figure 9 The CAPE, Ti3C2, Ag2O2, and TCAg groups all demonstrated varying degrees of ability to disrupt bacterial biofilms, causing them to shrink or even rupture. The TCAg group exhibited the best disruptive effect.

[0054] Example 10: Pharmacodynamic evaluation of TAG@SMP and TCAg@SMP prepared in Examples 2 and 3 for treating periodontitis in rats. A rat model of periodontitis was established by ligation with silk sutures combined with injections of *Porphyromonas gingivalis* and *Fusobacterium nucleatum*. The specific procedure was as follows: After one week of acclimatization feeding, all rats except the control group were anesthetized intraperitoneally with 3% sodium pentobarbital (30 mg / kg). The rats were placed in a supine position, their heads and limbs were fixed, and the upper and lower jaws were pulled to fully expose the left maxillary molar. Then, the left maxillary second molar was ligated with 4-0 silk sutures and injected with *Porphyromonas gingivalis* and *Fusobacterium nucleatum* (total concentration 10%). 7CFU / mL, 100 μL). During the process, check for any suture slippage; if slippage occurs, re-ligate promptly and observe for periodontal pocket formation. Rats with successful modeling were randomly divided into: normal group, model group, positive control group (PERIO), TAG@SMP group, and TCAg@SMP group. Every 3 days, 100 μL of the corresponding preparation was injected submucospermically into the buccal and palatal central alveolar ridge crest of the maxillary first molar. The normal group and model group received the same volume of physiological saline. The TAG@SMP group and TCAg@SMP group underwent ultrasound (frequency 1 MHz, duty cycle 50%, power 1 W / cm²) after administration. 2 Two minutes later, UV curing was performed, and the drug was administered continuously for 4 weeks. After 4 weeks, rats were euthanized by intraperitoneal injection of an excessive amount of sodium pentobarbital. The left maxilla was separated, and excess soft tissue was removed with fine scissors. The specimen was then fixed in 4% paraformaldehyde for 48 hours. The tooth specimens were removed and placed in 10% EDT solution for decalcification, followed by graded ethanol dehydration, paraffin embedding, sectioning, and fish staining.

[0055] Fish fluorescence in situ hybridization sections were used. Figure 10 The results showed that the model group exhibited a large amount of *Porphyromonas gingivalis* (red) and *Fusobacterium nucleatum* (green) invading the gingival tissue, while the TCAg@SMP group showed the lowest amount of *Porphyromonas gingivalis* (red) and *Fusobacterium nucleatum* (green) invading the gingival tissue. This indicates that TCAg@SMP has a good antibacterial effect.

[0056] To investigate alveolar bone repair, Micro-CT scans were used to examine the alveolar bone of the first maxillary molar in rats. Results are as follows: Figure 11 As shown, the model group exhibited significant alveolar bone defects, exposed tooth roots, and obvious root bifurcation, indicating the successful establishment of the rat periodontitis model. The TAg@SMP group showed some degree of alveolar bone repair, with a significantly shortened distance from the cementoenamel junction to the alveolar ridge crest. The TCAg@SMP group showed significant alveolar bone recovery, approaching that of the normal group.

[0057] Example 11: The healing effect of TAG@SMP and TCAg@SMP gels prepared in Examples 2 and 3 on MRSA-infected mouse wound model. A mouse model of infected wounds was established by creating a wound area with a diameter of approximately 8 mm on the back of male C57BL / 6J mice (8-10 weeks old), followed by inoculation with 20 μL of MRSA bacteria. Mice were randomly assigned to groups and administered the following drugs: PBS (200 μL), Befojug gel (200 μL) for the positive control group, sterile physiological saline (200 μL), TAG@SMP (200 μL), and TCAg@SMP (200 μL). Following drug administration, ultrasound (frequency 1 MHz, duty cycle 50%, power 1 W / cm²) was used. 2Two minutes later, and the wound was closely monitored during the experiment.

[0058] The results are as follows Figure 12 As shown, by monitoring the entire wound healing process, it was found that TAG@SMP gel improved wound healing efficiency, and the wound began to close at an accelerated rate on day 7. In addition, TCAg@SMP had the fastest wound healing rate, which was significantly better than other groups.

Claims

1. A method for preparing an acoustically driven Janus hydrogel, characterized in that: Includes the following steps: (1) Preparation of precursor solution A: Titanium carbide nanosheets loaded with silver peroxide and / or phenethyl caffeate, photoinitiator LAP and methacrylamide silk fibroin were dissolved in deionized water and mixed evenly to obtain precursor solution A; the titanium carbide nanosheets loaded with silver peroxide and / or phenethyl caffeate were obtained by modifying titanium carbide nanosheets with aminosilane to obtain Ti3C2-NH2; then Ti3C2-NH2 was dissolved in ethanol solution, silver peroxide and / or phenethyl caffeate were added in sequence, stirred, and then centrifuged and washed to obtain the precipitate; (2) Preparation of precursor solution B: Dissolve γ-polyglutamic acid-N-hydroxysuccinimide ester in NaHCO3 solution to obtain precursor solution B; (3) Ultraviolet curing: Precursor solution A and precursor solution B are mixed and cured by ultrasound and ultraviolet light to obtain acoustically driven Janus hydrogel; In the hydrogel, the mass ratio of photoinitiator, titanium carbide nanosheets loaded with silver peroxide and / or caffeic acid phenethyl ester, methacrylamide silk fibroin and γ-polyglutamic acid-N-hydroxysuccinimide ester is 1:40:40-120:

40.

2. The method for preparing the acoustically driven Janus hydrogel according to claim 1, characterized in that: The stirring temperature is 25-37℃, and the stirring time is 4-24 hours; the mass ratio of Ti3C2-NH2 to phenethyl caffeate is 1:15-30; the mass ratio of Ti3C2-NH2 to silver peroxide is 1:1-3.

3. An acoustically driven Janus hydrogel, prepared by the preparation method described in claim 1 or 2.

4. The use of the acoustically driven Janus hydrogel according to claim 3 in the preparation of drugs for the prevention or treatment of periodontitis or oral mucositis.

5. The application of the acoustically driven Janus hydrogel according to claim 3 in the preparation of skin wound repair materials.

Citation Information

Patent Citations

  • Injectable temperature-sensitive viscous hydrogel for periodontitis treatment and medical instrument thereof

    CN117771164A

  • Hydrogel for oral periodontitis and preparation method thereof

    CN119019474A